2018
DOI: 10.1016/j.amjcard.2018.04.047
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Echocardiographic Markers of Left Atrial Fibrosis to Atrial Fibrillation Burden

Abstract: In patients with atrial fibrillation (AF), left atrial (LA) fibrosis is a major determinant of the progression to, and burden of AF. LA reservoir strain and total atrial conduction time (PA-TDI) reflect LA fibrotic content. We aimed to investigate the relation between LA reservoir strain and PA-TDI in AF patients and control subjects. Six-hundred two patients (mean age 56 years, 53% men) with first episode of AF and 342 controls (mean age 64 years, 71% men) without structural heart disease underwent echocardio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 30 publications
2
33
0
2
Order By: Relevance
“…These findings suggest that in hypertensive patients changes in the LA myocardium occur very early and support the role of LA strain imaging as an important and a very sensitive marker of hypertensive heart disease [ 22 ]. Recent data from Melissa Leung that links decreased LA reservoir strain with LA fibrosis, a fundamental component of hypertensive heart disease and AF, makes it even more valid and relevant in these conditions [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that in hypertensive patients changes in the LA myocardium occur very early and support the role of LA strain imaging as an important and a very sensitive marker of hypertensive heart disease [ 22 ]. Recent data from Melissa Leung that links decreased LA reservoir strain with LA fibrosis, a fundamental component of hypertensive heart disease and AF, makes it even more valid and relevant in these conditions [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…This atrial arrhythmia may itself lead to impaired LAS [16,17,18]. It was also suggested that the LASr value proved to be a strong parameter of LA brosis in patients with AF [19].…”
Section: Discussionmentioning
confidence: 99%
“…For this purpose, LA works as reservoir during ventricular systole, when it receives blood from pulmonary veins and its volume increases, as conduit during early ventricular diastole, passively allowing the passage of blood into the ventricle, and as booster pump during late ventricular diastole, when it actively contracts to complete LV filling. During last years the application of 2DSTE to the LA has been largely investigated in several studies [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. Longitudinal strain and SR curves are generated for each of the 6 atrial segments, obtained from apical 4- and 2-chamber views.…”
Section: Left Atrial Strainmentioning
confidence: 99%